Pengaruh Model Pembelajaran Treffinger terhadap Kemampuan Menulis Teks Laporan Hasil Observasi pada Siswa Kelas VII di SMP Negeri 2 Tapian Dolok - Theresia Annori Purba; Jumaria Sirait; Martua Reynhat Sitanggang Gusar (Medan Resource Center, 2022)
This study aims to determine: (1) the ability to write a text report on the results of observations in class VII students at SMP Negeri 2 Tapian Dolok before using the Treffinger learning model, (2) the ability to write a text report on the results of observations in class VII students at SMP Negeri 2 Tapian Dolok. after using the Treffinger model and, (3) to find out whether there is an effect using the Treffinger learning model in writing a report text on the results of observations of class VII students at SMP Negeri 2 Tapian Dolok. This research uses quantitative research using experimental methods, while the method used in this research is Pre-Experimental Design (non-design). According to Sugiyono (2019:112) that the results of Pre-Experimental research are independent variables. This happens, because there is no control variable, and the sample is not chosen at random. This study also uses the One-Group Pretest-Posttest Design. The results of this study include: (1) The results of the initial test ability (pre-test) in the skills of writing report texts on the observations of class VII-4 students of SMP Negeri 2 Tapian Dolok before the treffinger learning model is applied, the average value is 39.66 with a total 1.190 From the results (pre-test) obtained by students that the ability to write text reports on observations has not reached the KKM target (Minimum Completeness Criteria) which is 70. (2) The results of the final test (post-test) ability in writing report text skills on class observations VII-4 SMP Negeri 2 Tapian Dolok after applying the treffinger learning model, the average score was 76.96 with a total score of 2.309. From the results (post-test) obtained by students in writing the text of the report on the observation results, they have reached the KKM target (Minimum Completeness Criteria) which is 70. (3) The analysis has been carried out and has been tested statistically that tcount is greater than ttable (9,34>1.699) then causes H0 to be rejected and Ha to be accepted. Thus, it can be concluded that there is an effect of the treffinger learning model on the ability to write text reports on observations in class VII-4 of SMP Negeri 2 Tapian Dolok.